For the first part:Every shirt she grabs, will cost her dollars, so if she grabs 3 shirts, then the cost of the shirts is:
![12+12+12=3(12)](https://tex.z-dn.net/?f=12%2B12%2B12%3D3%2812%29)
With the same rationale, if she grabs 2 pairs of jeans, the cost of the jeans is:
![19+19=2(19)](https://tex.z-dn.net/?f=19%2B19%3D2%2819%29)
So, her total is:
![3(12)+2(19)](https://tex.z-dn.net/?f=3%2812%29%2B2%2819%29)
If you subtract 3 from the total, then the expression is:
For the second part:If she's paying 3 less for each shirt, then the cost of 3 shirts will become:
![(12-3)+(12-3)+(12-3)=3(12-3)](https://tex.z-dn.net/?f=%2812-3%29%2B%2812-3%29%2B%2812-3%29%3D3%2812-3%29)
In the same fashion, for the two jeans:
![(19-3)+(19-3)=2(19-3)](https://tex.z-dn.net/?f=%2819-3%29%2B%2819-3%29%3D2%2819-3%29)
So the expression for the total cost is:
For number three:The amounts are different because the cost of the total purchase is different than the cost of each element that makes up the total purchase.
For number four:If you're the owner, you want to give the smallest amount of discount (the one in part 1/a).
So you could clarify by saying there's 3 dollars of the TOTAL purchase's cost.